Control and prevention of brucellosis in dairy cattle in syria (Journal of Hama University, 2022)
The study confirmed that dairy herds in governmental were free of any positive cases of infectious Abortion Disease caused by Brucella abortion agent.While dairy cattle data in private sector farms the prevalence proportion ranged between the value zero in south Aleppo province to /7/% in north Hama province regions with total prevalence of all study herds in Syria /4.72/%. The study reported increase in the prevalence with advance ages categories as reported in the present study proportion prevalence in ages less than 2 years /3.49/% and increase in ages up to 4 years to 6.4% and then increase the proportion up to 5 years ages to pointed out /11.56/ as proportional prevalence, then the prevalence was decrease again in ages more than 5 years to point out /10.78/. The study was undertaken field of sides of control and prevention of disease via using theoretical epidemiological modeling of infections in relation with time agent, it was studied the vaccine efficiency covering in vaccinated animals and determine the rage of vaccination timing in studied cattle herds through the measuring of vaccine efficiency via assumptive theoretical study.The study was included the economic impact of Brucella- abortuos and evolution the efficiency of variant program in control and prevention up to achieve the requirements of profit program and cost of the economic study of the mentioned disease in a precision form. The results showed using LPEC program thatcontrol of Brucella abortuos can be maintain of the productivity efficiency.